Jargon Pengemudi Gojek Brebes Tegal Slawi dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia Di SMA - Mohamad Dimas Triwicaksono; Leli Triana; Vita Ika Sari (Peneliti.net, 2020)
The diversity and differences in backgrounds of every individual in a society that is not homogeneous, causing various language variations in every interaction or social communication carried out by the community. Likewise in the Gojek driver community, diverse backgrounds have led to variations in language and jargon. The purpose of this study is to describe the jargon of the Brebes, Tegal, Slawi gojek drivers, describing the factors that cause the use of jargon by the Brebes, Tegal, Slawi, and Describe the implications of research results in language learning in high school. This research is a qualitative descriptive study with sociolinguistic theory. The data in this study is in the form of jargon from the Gojek driver. Provision of data in this study using a competent, free listening technique. Data were analyzed using pragmatic and distributional equivalent methods or the aggregate method. The results of this study indicate that the form of jargon used by Gojek Brebes, Tegal, Slawi drivers is divided into five word formations, namely four basic words, four words of influence, one repeated word, one compound word, and seven abbreviations. Factors causing the use of jargon by the driver, namely five due to the subject and twelve due to social speakers.